Weathering and erosion - Jankowski, Laurence J., Dr (Physical geography series)
This program explores how the surface of the earth is in constant struggle with the elements. Wind, running water, gravity and temperature changes break down rock formations and carry away material to build up deltas, beaches, geosynclines and dunes. This program was filmed all over America.